(The Role of Information Management Systems in Improving the Quality of Learning in Muhammadiyah Vocational Schools in Bandung City) - yanto, nopiyanto nopi; Mahmudah, Fitri Nur (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The development of a school information system aims to make it easier for all school members to access information efficiently and effectively, therefore a school management information system must be implemented in a school to make decisions. The education section has an important role in the education management information system, especially in planning, monitoring, monitoring, evaluation. Apart from that, this research aims to discuss further the implementation of management information systems to improve the quality of learning services in vocational schools. A qualitative approach is used in this research. The research population at Muhammadiyah Vocational Schools in Bandung City. This research aims to find out how to plan the implementation and evaluation of information systems in schools. improve the quality of learning in schools based on research results showing that the use of school management information systems has been implemented well by schools and can improve student learning outcomes